Effect of cinnamon powder addition to a Portuguese custard tart (Pastel de Nata) on healthy adults’ postprandial glycemia - Moncada, M. M. (2017)
Background and Objective: Cinnamon is a spice used over the years in cooking to impart aromatic, flavor and taste properties to food and beverages. Moreover, cinnamon has been used for its medicinal properties due to its potential phenolic content, which can protect against cardio-metabolic diseases. Previous studies reported an improvement of postprandial glycemia after addition of cinnamon powder to a high-sugar meal. The study aims at investigating the effect of adding cinnamon powder to a Portuguese custard tart (Pastel de Nata) on the postprandial glycemic response in healthy subjects. Subjects and Methods: After review board and Ethic Committee of the State approval, thirty-two healthy human subjects were assigned in a controlled study and randomly allocated into 2 groups: 16 subjects ingested a custard tart with cinnamon powder (cinnamon group) and 16 subjects ingested a custard tart alone (control group). Blood glucose concentrations were measured before interventions and after 30, 60, 90 and 120 minutes. Chemical analysis was performed to quantify the total phenolic content and antioxidant activity. Results: The postprandial blood glucose (PBG) area under the curve (AUC) was significantly lower (p = 0.0005) in the cinnamon group (599.2 ± 9.1) compared to the AUC of the control group (645.7 ± 7.7). The administration of cinnamon powder to the custard tarts slightly decreased PBG mean values compared to custard tart without cinnamon powder, although it did not reach statistical significance (p = 0.273). Cinnamon addition to custard tart improved the total phenolic content (1278.7 ± 0.7 compared to 253.7 ± 22.8 mg/L gallic acid) and antioxidant properties, increasing 4.4 times the capacity of free-radical scavenger compared with custard tart without cinnamon (IC50). Conclusion: The addition of cinnamon powder to custard tart could be beneficial to glycemic control.